PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN BATIK JAMBI - Masrita . (Jurnal Dinamika Manajemen, 2013)
The aim of this study is to determine the effect of the marketing mix variables such as product, price, promotion and distribution of the purchasing decision Jambi batik and to determine the dominant factor that can influencer the purcvhase decision is price. The sampling technique used sampling probability. Furthermore to test the hypotesis, F test and t test are used. The results shows that the four marketing mix variables product, price, promotion, distribution of significance to the purchasing decision Jambi batik. Hypothesis testing using t test showed that all four independent variables found to significantly affect the dependent variable purchase decision. Then through the F test can be seen that the variable product, price, promotion, and distributionhave significanton purchasing decision. Keywords: Product, Price, Promotion, Distribution, Buying Decision